2019
DOI: 10.1002/cam4.2207
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic stem cell microenvironment suppresses the malignancy of cutaneous melanoma cells by down‐regulating PI3K/AKT pathway

Abstract: Malignant cancer cells engage in a dynamic reciprocity with the tumor microenvironment (TME) that promotes tumor growth, development, and resistance to therapy. Early embryonic blastocyst microenvironments can reverse the tumorigenic phenotype of malignant cancer cells via ameliorating of TME. It is potential to apply embryonic stem cell (ESC) microenvironment to suppress the malignant behaviors of cancer cells. This study aimed to investigate a better method and the mechanism of ESC microenvironment supplied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…Western blotting confirmed that the expression of pro-apoptosis genes Bcl-2, p53, Bax and Caspase3 in U118 cells of GE co-culture group was significantly higher than the control group according to Figure 3D,3E. [13][14][15]. We attempted to use ES cells on a mouse leukemia model and we found that ES cells could significantly improve myelography of mice and prolong their survival.…”
Section: Es Microenvironment Inhibits the Proliferative Ability Of U1mentioning
confidence: 86%
See 1 more Smart Citation
“…Western blotting confirmed that the expression of pro-apoptosis genes Bcl-2, p53, Bax and Caspase3 in U118 cells of GE co-culture group was significantly higher than the control group according to Figure 3D,3E. [13][14][15]. We attempted to use ES cells on a mouse leukemia model and we found that ES cells could significantly improve myelography of mice and prolong their survival.…”
Section: Es Microenvironment Inhibits the Proliferative Ability Of U1mentioning
confidence: 86%
“…Researchers have successfully used the embryonic stem cells to simulate the microenvironment of embryos, confirmed their safety and efficacy in the treatment of leukemic mice, [13] and found that embryonic stem cell microenvironment can reverse the degree of malignancy of uveal melanoma and cutaneous melanoma by downregulating PI3K pathway [14,15]. This study aimed to investigate whether embryonic stem cell microenvironment can reverse the degree of malignancy of human glioma.…”
mentioning
confidence: 96%
“…The ability of the embryonic microenvironment to reverse tumor cells gradually diminishes as the embryo develops and differentiates. Gerschenson et al (21) injected melanoma cells into E10 mouse embryos (12)(13)(14), E14 mouse embryos, and the dorsal skin of newborn mice. The tumor formation rates were 0 (0/5), 73% (32/44), and 80% (16/20), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, researchers gradually turn their attention to stem cell therapy because of the unmet need for cancer treatment. Since early experiments showed that the zebrafish embryonic environment can reverse the malignant phenotype of cancer (Lee et al, 2005), inspired by this, our laboratory also studied the embryonic stem cell microenvironment (ESC‐ME) and found that ESC‐ME could not only inhibit the malignant behaviors of skin (Wang et al, 2019) and uveal melanoma, but also resist the aging of normal cells and promote their proliferation (Liu et al, 2019). EVs are currently proven to play a key role in the microenvironment of stem cells, thus the effectiveness of SC‐EVs to concurrent reverse aging and anticancer has been preliminarily confirmed.…”
Section: The Relationship Between Evs and Cancer And The Way Sc‐evs Amentioning
confidence: 99%